PENGARUH METODE DRILL BERBANTUAN MEDIA AUDIO TERHADAP KETERAMPILAN MENYIMAK CERITA DI SD - Sari, Diah Prandita; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to analyze the influence of the drill learning method assisted audio media on children story listening skills of fifth grade students on Public Elementary School 09 East Pontianak. This study uses an exsperimental method with a quasi exsperimental design of non equvalent control group design. The population is all students from five classes totaling 96 students. The sampling technique uses purposive sampling. Data collection techniques are measurement techniques, with data collection tools are multiple choice tests. The result of data analysis are, the average post-test experimental class = 79,77 and average post-test result of the control class = 72,5. Based on the results of the t-test calculation obtained by tcount 2.73>ttable 1.98, then Ha is accepted, which means there is a significant influence on the use of drill learning method assisted audio media. From the calculation of the effect size (d), obtained (d) of 0,69 with medium criteria.Means the use of drill learning method assisted audio media has a medium influence on children story listening skills of fifth grade students on Public Elementary School 09 East Pontianak.Â Keywords: Audio Media, Drill Learning Method, Listening Skills